ANALISIS POTENSI BAHAYA MENGGUNAKAN METODE CHECKLIST SEBAGAI UPAYA PENCEGAHAN KECELAKAAN KERJA CV. SURYA AGRITAMA INDONESIA - Zainal Abidin Akh. Sokhibi (Universitas Muria Kudus, 2021)
A work accident is an event that humans do not want to experience. Accidents are a big problem for the survival of the company because they can cause substantial material losses as well as fatalities and occupational diseases. Efforts to improve occupational safety and health in every industry are a way to avoid these occupational accidents. CV Surya Agritama Indonesia is a manufacturing company that manufactures product namely rubber rolls, As a rubber rolls manufacturing company, CV. Surya Agritama whose every work process cannot be separated from potential dangers. This study aims to determine the risk of work accidents in CV. Surya Agritama Indonesia, the method used to complete this research is the checklist method by collecting data by means of interviews and observations The results of the study show that there are 2 fields that result in fatal work accidents, namely the production and B3 fields, the risk value involved in extreme risk is 60% with 30% production machines and 30% B3 materials, 22% high risk with the work environment, 11% medium risk with Workers, and 7% low risk with security